FORMULASI TABLET SERBUK PISANG RAJA (Musa xparadisiaca AAB) SEBAGAI PENUTUP TUKAK LAMBUNG PADA TIKUS - Iis Wahyuningsih (Universitas Ahmad Dahlan, 2012)
Mucoadhesive is a topic of current interest in the design of drug delivery systemand treatment of peptic ulcers. This concept is based on the strength of adhesion of aprotective material to the mucosa. King Banana (Musa xparadisiaca AAB) is oftenused in the treatment of abdominal pain. It has been suspected having muchoadhesivestrength to cover peptic ulcer. The study was armed to formulate king banana tabletwhich has muchoadhesive ability to protect gastric mucosa become ulcer. The aim ofpeptic ulcer cover test was to see the ability of king banana tablet to covered ulcer at thegroups test that received different treatment of the negative control group (solvent), thebanana tablet suspension group, and sucralfate group. The ulcer severity wasdetermined by scoring method. All experimental data were tested by SPSS analyticalstatistics. The result showed that king banana tablet has similar strength to peptic ulcercover of sucralfat and not significantly different.